Climate Change Impacts and Adaptation Strategies for Ethiopia’s Coffee Sector: A Review - Bekele, Teka Tefera (Journal of Coffee and Sustainability, 2025)
Ethiopia, the birthplace of Arabica coffee, faces significant challenges from climate change, threatening a sector that supports over 15 million smallholder farmers. This review synthesizes research from 2010-2023, systematically sourced from Scopus, Web of Science, and Google Scholar, prioritizing peer-reviewed journals and key institutional reports. The selection criteria focused on recent studies (post-2018) and those providing specific data on Ethiopia's coffee-growing regions. The analysis reveals a historical temperature rise of 1.3°C since the 1960s, with projections of a further 1.4–2.9°C increase by the 2060s. However, a key limitation identified is the lack of localized climate models, which constrains the reliability of projections for specific agro-ecological zones. Despite this uncertainty, the consensus indicates these changes could reduce suitable coffee-growing areas by up to 60%, exacerbating pests and diseases and risking the livelihoods of 1.5 million farmers by 2050. Key adaptation and mitigation strategies—such as agroforestry, drought-resistant varieties, and renewable energy adoption—are evaluated. The review concludes by highlighting critical gaps in localized modeling and socio-economic integration, calling for urgent, targeted action to safeguard Ethiopia's coffee sector.